PEMANFAATAN PATI TALAS (Colocasia esculenta (L.) Schott) SEBAGAI BAHAN SUBSTTTUSI TEPUNG TERIGU DALAM PEMBUATAN ROTI MANIS - JONI RIANTO (JURNAL ILMIAH KOHESI, 2018)
This research was aimed to know the nutrient value, physical characteristic and effort of acceptanceconsumer. The treatment in this research are A (without substitution), B (substitution 5%), C(substitution 5%), D (substitution 10%), E (substitution 15%) and F (substitution 25%). The chemicalcharacteristic was analyzed are moisture, protein, starch and sugar content. While The physicalcharacteristic of sweet bread was analyzed with straight dough level and bread volume. Organoleptic testincluded hedonic test for colour, textur, taste and flavor. The result of research obtained that the sweetbread with substitution 20% from organoleptic test was acceptanced by panelist with moisture content of9.67%, protein content of 3.89%, starch content of 24.65%, sugar content of 8.22%, straight level dough of1,37 cm3per 50 g and bread volume of130 cm1 per 50 g.